Implementing curriculum reform in Wales: the case of the Foundation Phase. (3rd May 2016) - Taylor, Chris; Rhys, Mirain; Waldron, Sam
Abstract: The Foundation Phase is a Welsh Government flagship policy of early years education (for 3–7 year-old children) in Wales. Marking a radical departure from the more formal, competency-based approach associated with the previous Key Stage 1 National Curriculum, it advocates a developmental, experiential, play-based approach to teaching and learning. The learning country: A paving document (NAfW, 2001) notes that, following devolution, Wales intended to take its own policy direction in order to 'get the best for Wales'. Building on a three-year mixed methods independent evaluation of the Foundation Phase we discuss in detail the aims and objectives of the Foundation Phase, including the context to its introduction, the theory, assumptions and evidence underlying its rationale, and its content and key inputs. We then contrast this with how the Foundation Phase was received by practitioners and parents, how it has been implemented in classrooms and non-maintained settings, and what discernible impact it has had on young children's educational outcomes. The paper concludes with a critical analysis of the policy process and identifies a number of contextual issues during the inception of the Foundation Phase that has, it could be argued, constrained its development and subsequent impact. We argue that these constraints are associated with an educational policy landscape that was still in its infancy. In order for future education policy to 'get the best for Wales' a number of important lessons must be learnt.